Green eggs and ham - Seuss (Living Books San Francisco, CA, 1996)
Multimedia adaptation of the Dr. Seuss book in which Sam-I-Am tries to determine under what circumstances the old man will eat ham and green eggs. Features animation, games, activities, and Read-to-Me mode. Assists in the development of word recognition, vocabulary building, reading comprehension, and computer literacy